Jenis Keragaman Peserta Didik Dalam Pembelajaran - Tresna Wati; Iga Selvia Sari; Opi Andriani (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the types of children's diversity in learning. The method used in the research is literature study or literature review. There are 2 journals that are suitable for this research. The results of this research show that children's diversity in learning is a phenomenon that is increasingly recognized as a key aspect in education. Children bring a variety of backgrounds, cultures, interests, and abilities to their learning environment. By embracing diversity, educators can create an inclusive environment and allow every child to develop to their potential.